2019
DOI: 10.1042/bsr20191661
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of protein acetyltransferases of human pathogen Mycobacterium tuberculosis

Abstract: Tuberculosis (TB), a leading infectious disease caused by Mycobacterium tuberculosis strain, takes four human lives every minute globally. Paucity of knowledge on M. tuberculosis virulence and antibiotic resistance is the major challenge for tuberculosis control. We have identified 47 acetyltransferases in the M. tuberculosis, which use diverse substrates including antibiotic, amino acids, and other chemical molecules. Through comparative analysis of the protein file of the virulent M. tuberculosis H37Rv strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…Here, we demonstrated that miR-625-5p targeted ZEB2 in BC cells. Of course, other miRNAs could interact ZEB2 to regulate the occurrence and progression of BC; multiple miRNAs, including miR-30a [ 21 ], miR-653 [ 22 ], miR-448 [ 23 ], and miR-124 [ 24 ] were identified to bind to the 3′UTR of ZEB2 in BC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we demonstrated that miR-625-5p targeted ZEB2 in BC cells. Of course, other miRNAs could interact ZEB2 to regulate the occurrence and progression of BC; multiple miRNAs, including miR-30a [ 21 ], miR-653 [ 22 ], miR-448 [ 23 ], and miR-124 [ 24 ] were identified to bind to the 3′UTR of ZEB2 in BC cells.…”
Section: Discussionmentioning
confidence: 99%
“…The diversity of protein functions is facilitated by PTM that changes the structure/function relationship and affects the formation of protein complexes, enzyme catalysis, and other biomolecular interactions ( Cain et al, 2014 ). In recent years, accumulating evidence indicates that PTMs play a critical role in various physiological processes, such as immunometabolism ( Diskin et al, 2020 ), protein synthesis and turnover ( Rioseras et al, 2018 ), protein stability ( Ishigaki et al, 2017 ; Sang et al, 2017 ), dormancy ( Yang et al, 2018 ), nitrogen metabolism ( Macek et al, 2019 ), and virulence ( Xie et al, 2019 ). Among the hundreds of diverse PTMs, protein phosphorylation, acetylation, succinylation, pupylation and ubiquitin-like modifications, glycosylation, and lipidation play a major role in regulating bacterial cell cycle, cell metabolism, persistence, and virulence ( Ren et al, 2016 , 2019 ; Macek et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hundreds of succinylation sites and proteins have been identified in a variety of microorganisms. Various bacteria [ 23 ] and fungi, such as Escherichia coli , Mycobacterium tuberculosis and Toxoplasma gondii , have been shown to undergo succinylation [ 24 , 25 ]. A systematic analysis of mammalian succinylation sites in mouse cells [ 26 ] indicated that protein succinylation sites may affect enzymes involved in mitochondrial metabolism.…”
Section: Introductionmentioning
confidence: 99%